Application and evaluation of a rapid detection method based on two-dimensional PCR technology for hypervirulent Klebsiella pneumoniae - Zhu, Wenwen; Wang, Yiting; Jiang, Xin; Zhao, Yan (Frontiers in Microbiology, 2025)
ObjectivesHypervirulent K. pneumoniae (hvKp) is an emerging pathogen that is more virulent than classical K. pneumoniae (cKp). This study aimed to develop an economical, high-throughput, and accurate two-dimensional polymerase chain reaction (2D-PCR) assay for the rapid detection of hvKp.Materials and methodsRecombinant plasmids containing the iucA, peg-344, rmpA2, and rmpA virulence genes were constructed and used for assessing the sensitivity and specificity of the 2D-PCR. Clinical samples (n = 105) were collected and evaluated the performance of the 2D-PCR to comparison with conventional PCR methods.ResultsThe minimum detection limit of the 2D-PCR assay for iucA, peg-344, rmpA2, and rmpA were 103, 102, 103, and 103 copies/μL, respectively. Additionally, the concordance rates between the 2D-PCR and conventional PCR for detecting iucA, peg-344, rmpA2, and rmpA were all over 95%. The analysis revealed a sensitivity of 100.0% and a specificity of 96.2% when compared to conventional PCR.ConclusionA 2D-PCR-based multiplex method for virulence genes of hvKp was successfully developed, demonstrating its outstanding features of high specificity, high sensitivity, and high throughput capability. This method could be used for the rapid diagnosis of infectious diseases caused by hvKp in clinical settings.